The use of a- amylase and pullulanase enzymes in wellbore cleaning - Masseera Mahictin, 1987-, author; Issham Ismail, supervisor; Rosli Md. Illias, supervisor; Fakulti Kejuruteraan Petroleum dan Kejuruteraan Tenaga Diperbaharui (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2012)
Thesis (Sarjana Kejuruteraan (Petroleum)) - Universiti Teknologi Malaysia, 2012